2005
DOI: 10.1038/nbt1088
|View full text |Cite
|
Sign up to set email alerts
|

Migration and differentiation of neural precursors derived from human embryonic stem cells in the rat brain

Abstract: Human embryonic stem (hES) cells provide a potentially unlimited cell source for regenerative medicine. Recently, differentiation strategies were developed to direct hES cells towards neural fates in vitro. However, the interaction of hES cell progeny with the adult brain environment remains unexplored. Here we report that hES cell-derived neural precursors differentiate into neurons, astrocytes and oligodendrocytes in the normal and lesioned brain of young adult rats and migrate extensively along white matter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
127
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(138 citation statements)
references
References 27 publications
8
127
0
Order By: Relevance
“…Tumor formation and graft overgrowth [45][46][47] from pluripotent stem cells and their derivatives are major hurdles for the application of stem cell therapy in stroke and other brain diseases. In previous studies, human iPSCs showed high tumorigenicity after intracerebral implantation in stroke-damaged brain [24].…”
Section: Discussionmentioning
confidence: 99%
“…Tumor formation and graft overgrowth [45][46][47] from pluripotent stem cells and their derivatives are major hurdles for the application of stem cell therapy in stroke and other brain diseases. In previous studies, human iPSCs showed high tumorigenicity after intracerebral implantation in stroke-damaged brain [24].…”
Section: Discussionmentioning
confidence: 99%
“…The anatomical location and lineage specificities of NSCs were only established when they were finally identified in the subependymal region and in the hippocampal dentate gyrus (DG), where they divide to generate progenitors that migrate along the rostral migratory stream to differentiate in the olfactory bulb or to integrate into the surrounding hippocampal neural circuitry, respectively [26][27][28]. Similar to HSCs, these nestin+ NSCs may be defined operationally as cells that can continuously self-renew and have the potential to generate intermediate and mature cells of both glial and neural lineages [29].…”
Section: Neural Stem Cellsmentioning
confidence: 99%
“…While their exact function and distribution is currently being assessed, they represent an interesting cell population, which may be used to study factors important for the differentiation and characterization of neurons, astrocytes and oligodendrocytes. Recently, there have been reports of NSC transplantations attempting to achieve functional recovery from CNS damage [171][172][173][174][175][176], and recent evidence suggests that NSCs may be a suitable source for the treatment of neurological diseases [22][23][24][25][26][27][177][178][179]. Due to their proliferative and differentiation capacity, NSCs will be important in fighting numerous brain disorders like AD, PD and Huntington's disease, as well as spinal cord disorders.…”
Section: Clinical Relevance and Conclusionmentioning
confidence: 99%
“…1,2,[23][24][25] Since neurodegenerative diseases are in many cases lateonset diseases, we found therefore of interest to study the in vivo properties of control or Bcl-X L overexpressing hNS1 cells after transplantation into the aged rat brain. Consistent with the in vitro data, we have also observed an increased neuron production and a diminished glia yield from Bcl-X L -overexpressing hNS1 cell transplants.…”
mentioning
confidence: 99%